Genetic Polymorphisms of The Chicken Antiviral Mx Gene in A Variety of Indonesian Indigenous Chicken Breeds - Sulandari, Sri; Syamsul Arifin Zein, Moch; Astuti, Dwi; Sartika, Tike (Jurnal Veteriner; Vol 10 No 2 (2009), 2009)
It has previously been demonstrated that a G/A Single Nucleotide Polymorphism (SNP) at nucleotideposition 1,892 of coding sequence of chicken Mx gene confers susceptibility/resistance to avian viral diseases.The aim of this study was to assess the geographical distribution of G/A alleles in relation to differentgenetic backgrounds of a wide range of chicken populations. Using Polymerase Chain Reaction- RestrictionFragment Length Polymorphism (PCR-RFLP) methods, 492 samples from 15 breeds of indigenous chickenpopulations from Java, Sumatera, Kalimantan and Sulawesi islands were genotyped. Allele and genotypefrequencies of each population were calculated. Deviations from Hardy-Weinberg equilibrium were testedand inbreeding coefficient FIS estimated. Overall, the susceptible allele G had a frequency of 37.27% whilethe resistant allele A had a corresponding frequency of 62.73%. No clear relation of the geographicaldistribution of the G/A alleles to genetic backgrounds was found. The distribution of this SNP acrosspopulations seems to be affected by genetic drift rather than selection.
Keywords: Mx gene, allele frequency, genetic background, geographical distribution